In Vivo quantification of 4D modeling and remodeling in trabecular and cortical bone microstructure - Shyu, Peter T.; Robinson, Samuel T.; Guo, X. Edward (Frontiers in Medical Engineering, 2025)
Bone is constantly adapting each of its microstructural compartments by modeling and remodeling. These adaptations are delineated by whether bone formation and resorption are coupled in space and time. Time-lapse microCT imaging has become a valuable technique for characterizing bone dynamics in 3D. Our previous study used longitudinal microCT imaging to quantify modeling and remodeling across the bone microstructure in response to PTH treatment and mechanical loading. Here, we detail our technique of voxel-tracking to specifically identify time-dependent modeling and remodeling by examining the sequence of formation and resorption events in trabecular and cortical bone. We apply this technique to WT and SOST KO littermate mice under long-term mechanical loading and quantify site-specific bone volume changes. Loading particularly affected WT trabecular and periosteal bone by increasing anabolic modeling and remodeling while decreasing catabolic modeling. Under load-controlled loading, these effects were reduced in SOST KO mice. Endosteal bone was less responsive to loading for both genotypes, with subtler and more time-dependent responses resulting in a load-dependent increase in WT catabolic modeling. Thus, we present a technique that directly assesses longitudinal 3D bone modeling and remodeling across the bone microstructure.